Tsunami Vulnerability and Risk Assessment of Banda Aceh City through ArcGIS Software - Mery Silviana (Jurnal Inotera, 2020)
This research produced a tsunami risk map of village’s community in Banda Aceh from a low level to a high level risk. Disaster risk analysis techniques involve a set of multi-criteria and Geographic Information Systems (GIS). GIS is used as a method to evaluate the multi-criteria which are made into spatial data and combining them into a risk map. Disaster risk assessment involves two factors: the tsunami hazard assessment and vulnerability of community. Tsunami hazard’s level is measured based on the map of the tsunami’s intensity by the number of damaged buildings that is produced by JICA study team on the Indian Ocean Tsunami in 2004, while the vulnerability of community is evaluated from hazard exposure and coping capacity of society in social, economic and physical dimension. Result of study shows two villages that have an extremely high degree of risk, 36 villages have a high degree of risk, 11 villages have a medium risk, 12 villages have a low risk and 29 villages have no risk at all.